The effects of burning on isotope ratio values in modern bone: Importance of experimental design for forensic applications. (August 2022) - Sarancha, Julianne J.; Eerkens, Jelmer W.; Hopkins, Christopher J.; Gonçalves, David; Cunha, Eugénia; Oliveira-Santos, Inês; Vassalo, Ana; Gordon, Gwyneth W.
Abstract: This study examined preservation of isotope ratio values by comparing isotope composition of bones before and after burning. We analyzed common geoprofiling isotope systems ( δ 13 C, δ 15 N, δ 18 O, and 87 Sr/ 86 Sr) and lesser studied systems ( δ 34 S and δ 88/86 Sr) to evaluate if inferences about diet and residence history were altered by the burning process. We used two burn methods: one to simulate previous academic studies using a muffle furnace and one to more closely resemble a house fire or body disposal attempt using open flame. To mimic previous burn studies, ribs and femora from four dry modern human skeletons were heated in a muffle furnace. To resemble a forensic burn situation, fleshed pig ribs from a single geographic location were burned on an open fire both with and without use of a diesel accelerant. Isotope ratios from bone collagen, carbonate, phosphate, and strontium were analyzed. Fleshed pig samples burned in an open fire maintained unaltered isotope ratio values. Dry human samples burned in a muffle furnace maintained unaltered isotope ratio values in most isotope systems, except for δ 18 O values in carbonate and phosphate, which showed a depletion of 18 O at higher temperatures. This research suggests that the isotope composition of fleshed burned bone retains the geoprofiling inferences of unburned bone, at least within the parameters of the open fire burn used in this study. However, oxygen isotopes of carbonate and phosphate from dry bone burned in a muffle furnace do not retain the geoprofiling inferences. This research demonstrates the need for research using an experimental design relevant to a specific burn situation. Highlights: Isotope systems of C, N, S, and Sr are conserved in bones burned below calcination. Oxygen isotopes are poorly preserved in unfleshed bones burned at high temperatures. Fleshed pig bones preserve isotope ratio values better than unfleshed human bones. Isotope analysis of human remains burned with flesh can assist in identification. Future research should use a burn method relevant to burn conditions of interest.